HIGHER EDUCATION MANAGEMENT EFFECTIVENESS OF MANAGEMENT IN ORGANIZING WORK - Murodova Nodira Qulliyevna; Alimova Madina Abdikhalilovna (Zeta Repository, 2023)
This article describes management methods in the organization of higher education management work.